Parental social support, coping strategies, resilience factors, stress, anxiety and depression levels in parents of children with MPS III (Sanfilippo syndrome) or children with intellectual disabilities (ID). Issue 2 (15th November 2012) - Grant, Sheena; Cross, Elaine; Wraith, James Edmond; Jones, Simon; Mahon, Louise; Lomax, Michelle; Bigger, Brian; Hare, Dougal
Abstract: Mucopolysaccharidosis type III (MPS III, Sanfilippo syndrome) is a lysosomal storage disorder, caused by a deficiency in one of four enzymes involved in the catabolism of the glycosaminoglycan heparan sulphate. It is a degenerative disorder, with a progressive decline in children's intellectual and physical functioning. There is currently no cure for the disorder. To date there is a paucity of research on how this disorder impacts parents psychological functioning. Specifically, research in the area has failed to employ adequate control groups to assess if the impact of this disorder on parents psychological functioning differs from parenting a child with intellectual disability (ID). The current study examined child behaviour and parental psychological functioning in 23 parents of children with MPS III and 23 parents of children with ID. Parents completed postal questionnaires about their child's behaviour and abilities and their own psychological functioning. Parents of children with MPS III reported fewer behavioural difficulties as their child aged, more severe level of intellectual disability, and similar levels of perceived social support, coping techniques, stress, anxiety and depression levels as parents of children with ID. Both groups of parents scored above the clinical cut off for anxiety and depression. Parents of children with MPS III rated themselves as significantly less future‐orientated and goal directed than parents of children with ID. Services should develop support packages for parents of children with MPS III that incorporate an understanding of the unique stressors and current‐difficulty approach of this population. Future research should examine gender differences between parental psychological functioning, using mixed qualitative and quantitative approaches, and utilise matched developmental level and typically developing control groups.